Systematic Review with Network Meta-Analysis: Comparative Efficacy of Biologics in the Treatment of Moderately to Severely Active Ulcerative Colitis. - Adrian D Vickers; Claire Ainsworth; Reema Mody; Annika Bergman; Caroline S Ling; Jasmina Medjedovic; Michael Smyth (PLoS ONE)
Background Biological therapies are increasingly used to treat ulcerative colitis (UC). Aim To compare the efficacy of biologics in adults with moderately-to-severely active UC, stratified by prior exposure to anti-tumour necrosis factor (anti-TNF) therapy. Methods A systematic literature review was undertaken to identify studies of biologics approved for UC. Network meta-analysis was conducted for endpoints at induction and maintenance. Results Seven studies were included in the meta-analysis of induction treatment for anti-TNF therapy-naïve patients. All biologics were more effective than placebo in inducing clinical response, clinical remission, and mucosal healing. Infliximab demonstrated a statistically significant improvement over adalimumab in clinical response (odds ratio [OR] [95% credible interval (CrI)]: 2.19 [1.35-3.55]), clinical remission (OR [95% CrI]: 2.81 [1.49-5.49]), and mucosal healing (OR [95% CrI]: 2.23 [1.21-4.14]); there were no other significant differences between biologics for induction efficacy. Five studies were included in the meta-analysis of maintenance treatment, two studies rerandomised responder patients at end of induction, and three followed the same patients 'straight through'. To account for design differences, the number of responders at end of induction was assumed to be equivalent to the number rerandomised. Vedolizumab showed significantly different durable clinical response from comparators (OR [95% CrI] infliximab 3.18 [1.14-9.20], golimumab 2.33 [1.04-5.41], and adalimumab 3.96 [1.67-9.84]). In anti-TNF therapy-experienced patients, only vedolizumab and adalimumab could be compared. At induction, no significant differences in efficacy were seen. During maintenance, vedolizumab showed significantly improved rates of mucosal healing versus adalimumab (OR [95% CrI]: 6.72 [1.36-41.0]). Conclusions This study expands the understanding of comparative efficacies of biologic treatments for UC, encompassing outcomes and populations not previously studied. All biologic treatments were effective for UC during induction. Vedolizumab demonstrated possible clinical benefits in the maintenance setting versus all comparators, irrespective of prior anti-TNF exposure and after adjusting for differences in study design.